INNOVATION OF RECYCLING PLASTIC WASTE INTO ENVIRONMENTAL FRIENDLY PAVING BLOCKS - Juwairiah; Yusnia Sinambela; Meisi Riana; Efrizal Siregar; Nurianti Sitorus; Sofia Andriyanti (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This research is a design on the manufacture of environmentally friendly paving blocks from plastic waste. Paving block is a material that serves as a cover or hardening of the ground surface which can be one solution to deal with plastic problems. The data used by researchers in this study refers to primary and secondary data, primary data obtained directly by researchers in the field by testing the compressive strength at the age of paving blocks 2 and 7 days, namely 2.17 MPa and 28.99 MPa, absorption testing to water 0.76% and 0.59% has no effect on water absorption because plastic is a material that does not easily absorb water. As for the results of resistance testing to sodium sulfate, the results obtained are 0.25% and 0.59%. This is considered good because there are no cracks and physical damage to the paving block. It can be concluded that the used plastic used to make paving blocks meets the requirements of SNI-03-0691-1996 with class C quality.